Hypervascularity is more frequent in medullary thyroid carcinoma: Compared with papillary thyroid carcinoma. Issue 49 (December 2016) - Lai, Xingjian; Liu, Meijuan; Xia, Yu; Wang, Liang; Bi, Yalan; Li, Xiaoyi; Zhang, Bo; Yang, Meng; Dai, Qing; Jiang, Yuxin
Abstract : Abstract: This study was designed to retrospectively compare the sonographic features of medullary thyroid carcinoma (MTC) and the features of papillary thyroid carcinoma (PTC). A total of 97 patients with 127 MTCs between January 2000 and January 2016 and 107 consecutive patients with 132 PTCs were included in this study. Two radiologists retrospectively determined the sonographic features and compared the findings of MTCs and PTCs. Compared with the patients with PTCs, the patients with MTCs were older (46.9 years vs 42.9 years, P = 0.016) and the male proportion was higher (53.6% vs 33.6%, P = 0.005). Most of the MTCs had an irregular shape (72.4%), a length/width ratio <1 (75.6%), an unclear boundary (63.8%), no peripheral halo ring (93.7%), hypoechogenicity (96.9%), heterogeneous echotexture (76.4%), no cystic change (78.7%), calcification (63.8%), and hypervascularity (72.4%). There was no significant difference in the boundary, peripheral halo ring, echogenicity, and calcification between the MTCs and PTCs. However, compared with the PTCs, a larger size (2.2 vs 1.2 cm, P <0.001), a regular shape (27.6% vs 7.6%, P <0.001), a length/width ratio <1 (75.6% vs 51.5%, P <0.001), heterogeneous echotexture (76.4% vs 54.5%, P <0.001), cystic change (21.3 vs 8.3%, P = 0.005), and hypervascularity (72.4% vs 47.7%, P <0.001) were more frequent in the MTCs. The sonographic features with a higher likelihood of malignancy are common in MTCs, including a shape taller than the width, irregular infiltrative margins, an absent halo, hypoechogenicity, the presence of microcalcifications, and increased intranodular vascularity. However, MTCs tend to possess these suspicious sonographic features less often than PTCs, with the exception of hypervascularity, which was more frequent in MTCs. Abstract : Supplemental Digital Content is available in the text